A North American, single-center experience implanting fenestrated atrial devices and atrial flow regulators into a heterogeneous group of pediatric pulmonary hypertension patients - Youssef, David Edward; Averin, Konstantin; Richards, Susan; Sheppard, Catherine; Seaman, Cameron; Pietrosanu, Matthew; Bates, Angela (Frontiers in Pediatrics, 2023)
Introduction: The clinical deterioration commonly experienced by pediatric patients with pulmonary arterial hypertension (PAH) has motivated a shift in the treatment of pulmonary hypertension (PH) through innovations in surgical salvage interventions. The Occlutech fenestrated atrial septal defect (FASD) Occluder and the atrial flow regulator (AFR), which provides a protective, atrial-level shunt during hypertensive crises, have found an important role in treating pediatric patients with PAH. Other groups of pediatric patients with PH may also benefit from a similar protective physiology. The primary aim of this work is to present a single center’s experience with AFR and FASD devices for managing a heterogeneous group of pediatric PH patients. A secondary goal is to identify hemodynamic changes and complications following device implantation.